Dynamic Characteristics of the Gear Transmission System of a Hybrid Vehicle - Qin Pengfei; Zhang Xiong; Chen Bin; Fan Li; Su Zhanling; Wang Ruohuang (Jixie chuandong)
Taking the gear transmission system of a hybrid vehicle as the research object, the lumped parameter method is used to establish the dynamic model of the transmission system. Under the combined action of the eccentricity error, tooth frequency error, and time-varying meshing stiffness of each gear pair, the numerical method is used to solve the dynamic characteristics of the transmission gear under light-load, low-speed cruising and high-speed overtaking. The transmission system is coupled with the box body, the finite element model of the gear box is established, the dynamic meshing force of the gear is loaded, and the vibration characteristics of the box body during the switching process of the two working conditions are simulated using the Ansys software. A bench test for comparing and verifying the correctness of the dynamic model and simulation calculation is set up. The position of the box with the largest amplitude through the test is obtained, which provides a strong basis for optimizing the structure of the transmission system and improving the vibration characteristics of the gear box.